PELAKSANAAN PENGAWASAN TOKO OBAT OLEH BIDANG PEMERIKSAAN DAN PENYIDIKAN BALAI BESAR PENGAWAS OBAT DAN MAKANAN DI KOTA PEKANBARU - Putra, As Saffath Alfath; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Supervision means of drug distribution is important to provide protection to consumers against the dangers posed by drugs that are not fit for use anymore, already expired or does not have marketing authorization from the competent authority. The phenomenon in this study is the lack of supervision of BBPOM against drug trafficking without an authorization number on to protect the public from harm resulting from the unauthorized use of the drug. The concept of the theory is that researchers use repressive control by Brantas (2009). This research uses descriptive qualitative method of data collection techniques of observation, interviewing and research informants determined by snowball sampling technique. The samples taken are BBPOM Field Investigation in Pekanbaru.Keywords: Monitoring, Drug Stores, BBPOM